(untitled) (Plant Bulletin, 2024)
Garlic (Allium sativum L.) is a vital crop, yet its growth and sprouting at the green stage can be significantly influenced by nutrient availability, which poses a challenge for optimizing yield and quality. The present research was carried out in 2022–2023 at the Nursery Department of Horticulture, Sindh Agriculture University Tandojam, to assess the sprouting and growth of garlic (Allium sativum L.) at green stage under various nutrients. The experimental trial was carried out in complete randomization (CRD) with three replications. Two varieties, a Chinese and a local (Desi) (Desi) variety, were grown in the pots. Macronutrients used as treatments included N1 (control). N2 = NPK+TE (trace elements) 2 g, L-1. N3 = Calcium Nitrate 0.5g, L-1 and N4 = NPK+TE 2g, L-1 + Calcium Nitrate 0.5g, L-1. The results of the present studies showed a statistically significant difference for treatments and nutrient combinations. Best results for all observations were noted in plants supplied with NPK+TE 2g L-1 that had maximum plant height 55.83 cm, leaves plant-1 6.83, leaf length 47.66 cm, leaf weight 8.96g, plant weight 13.20g, neck thickness 6.55mm, root weight 2.68g, and root depth 19.83cm. Fallow control plant height 41.00cm leaves plant-1 5.00, leaf length 31.00cm, leaves weight 4.73g, plant weight 7.61g, neck thickness 3.51mm, root weight 1.46g and root depth 12.00cm. In between varieties the Chinese had maximum plant height 54.66cm, leaves plant-1 7.00, leaf length 45.00cm, leaves weight 10.04g, plant weight 10.99g, neck thickness 8.26mm, root weight 2.81g and root depth 22.00cm. Based on nutrients, the Chinese variety of garlic performed better growth at the green stage than the local (Desi) variety of garlic. The findings of this study show that nutrient N2 = NPK+TE (Trace Elements) 2g L-1had better results for all parameters, and all results were statistically significant.